An inventory of avian species in Aldesa Valley, Saudi Arabia - Abdulaziz S. Alatawi; Florent Bled; Jerrold L. Belant (Check List, 2018)
Conducting species inventories is important to provide baseline information essential for management and conservation. Aldesa Valley lies in the Tabuk Province of northwest Saudi Arabia and because of the presence of permanent water, is thought to contain high avian richness. We conducted an inventory of avian species in Aldesa Valley, using timed area-searches during May 10–August 10 in 2014 and 2015 to detect species occurrence. We detected 6860 birds belonging to 19 species. We also noted high human use of this area including agriculture and recreational activities. Maintaining species diversity is important in areas receiving anthropogenic pressures, and we encourage additional surveys to further identify species occurrence in Aldesa Valley.